Two-color pyrometer-based method for measuring temperature profiles and attenuation coefficients in a coal power plant. Issue 11 (2nd November 2018) - Lukovic, Milentije; Vicic, Milos; Popovic, Zoran; Zekovic, Ljubisa; Kasalica, Becko; Belca, Ivan
ABSTRACT: A novel method and the appropriate instrumentation for the measuring of temperature profiles and attenuation coefficients in a combustion chamber of a coal-fired power plant are described. The instrument is based on a two-color pyrometer. Results were verified by the pneumatic Venturi pyrometer measurements, as well as by sampling unburnt particles using a cooled extraction probe.